KEEFEKTIFAN MODEL PROJECT BASED LEARNING (PjBL) BERBANTUAN VIDEO KEARIFAN LOKAL DALAM KEMAMPUAN MENULIS CERPEN SISWA SMP - Fianjeli, Fifi; Irma Suryani; Helty Asafri (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to determine the effectiveness of the Project Based Learning (PjBL) model assisted by local wisdom videos in short story writing skills of junior high school students. The study used an experimental method with a One Group Pretest-Posttest Design. The subjects were 20 seventh grade students. Data collection techniques were in the form of short story writing tests analyzed using normality tests, homogeneity tests, t-tests, and N-Gain tests. The results showed a significant increase in the average pretest score of 11.65 to 13.90 in the posttest. The t-test results showed tcount (7.66) > ttable (1.7291) at the 0.05 level. The N-Gain value of 0.548 is included in the moderate category. Thus, the PjBL model assisted by local wisdom videos is effective in improving students' short story writing skills.